Perancangan Rak Baja Ringan Multifungsi Menggunakan Fitur Tambahan - Andriansyah, Hendri; Suhaerul, Muh Ledjanro Ramadhan; Julfin, Julfin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to design automatic lightweight steel shelves as a multifunctional solution in fish, chicken, and plant cultivation for family food independence. One of the main needs in various industrial and household sectors is a strong, flexible, and easily accessible storage system. Lightweight steel, with its corrosion-resistant, lightweight, and structurally sound characteristics, is the primary choice in multifunctional shelf designs. In the modern agricultural and livestock industry. One innovation that can be applied is the use of multifunctional automatic lightweight steel shelves. This study uses a qualitative descriptive approach with a focus on design planning using SketchUp software and budgeting. This study concludes that the design of this multifunctional automatic steel shelf can be a solution to the community's food needs.